ANTHROPOMETRIC VARIABLES IN BREAST LESIONS OF WOMEN OF REPRODUCTIVE AGE IN UNIVERSITY OF PORT HARCOURT TEACHING HOSPITAL - Orupabo, C. D.; Odoya, C. G. (International Journal of Medicine and Medical Research, 2023)
Background. Benign breast diseases are a potential health concern to a large number of women. The incidence of cancer is increasing worldwide. A steady increase in incidence has been observed in most developed and developing counties. Objective. Thus, our study seeks to investigate the anthropometric variables implicated in breast lesions of women of reproductive age. Methods. This is a descriptive and prospective study with a random sampling method; the data was obtained from the Department of Surgery, Radiotherapy and Oncology Unit of University of Port Harcourt Teaching Hospital. A total number of 146 subjects (18-49 years) were involved into this study. A number of 90 were breast lump patients and 56 were breast cancer patients. Results. Data obtained was analysed with Microsoft Excel. Our results show no statistically significant difference (P> 0.05) in the body mass index (BMI) and waist-hip-ratio (WHR) of both the breast lump and breast cancer patients. This study supports the fact that high BMI is a predictive marker for breast lumps and cancer in women. Conclusion. The study has also identified that high BMI favours the incidence of breast lumps and breast cancers in women of reproductive age.